Comparison of remineralizing efficacy of two novel preparation of arginine and theobromine on white spot lesion - an in vitro SEM analysis - Shifo Savio F; Nivethigaa Balakrishnan; Aravind Kumar Subramanian (Taylor & Francis Group, 2024)
Purpose Evaluation of the efficacy of two novel formulations of arginine and theobromine in remineralizing artificial enamel defects using in vitro testing techniques- Microhardness and SEMMaterials and methods Enamel slabs measuring 3 mm by 3 mm by 1.5 mm were created using 11 healthy premolars that were excised for orthodontic treatment. Group 1 (control, treated with merely a remineralization solution), Group 2 (0.05% arginine in 10 ml distilled water), and Group 3 (2% theobromine in 10 ml distilled water) were the three groups to which the slabs were randomly allocated (n = 7 per group). The pH cycle was run for 14 days, starting with a 72-h demineralization period and ending with 11 days of remineralization in the corresponding solutions. Prior to and during remineralization, microhardness was measured, and surface features were assessed using scanning electron microscopy (SEM). Statistical analysis, including Paired T Test, one-way ANOVA, and post hoc Tukey tests, determined that the mean values were significant at the 0.05 level.Results The control group showed a mean microhardness increase from 192.09 ± 19.30 to 208.58 ± 5.76. The arginine group increased significantly from 217.20 ± 4.24 to 304.00 ± 15.96, and the theobromine group from 214.09 ± 7.67 to 283.14 ± 10.91. Statistical analysis indicated that both arginine and theobromine groups had significantly greater microhardness improvements compared to the control (p < 0.05). SEM revealed that although arginine and theobromine enhanced enamel microhardness, surface morphology remained irregular and non-uniform.Conclusion Arginine and theobromine improve enamel microhardness and promote remineralization, but they do not create a uniform surface texture. Further research is needed to optimize their use and explore long-term effects on enamel surface uniformity.